Kajian Hukum Konstitusi terhadap Putusan Mahkamah Konsitusi Terkini: Usia Calon Presiden dan Calon Kepala Daerah - Sanmas, Rusdi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This study aims to analyze significant changes in Indonesia's constitutional law, particularly regarding the Constitutional Court's decision on the age limit for presidential and regional head candidates. Decision No. 78/PUU-XXI/2023 lowers the minimum age, previously set at 40 years, to be more inclusive for younger generations. Using a normative juridical approach, this research evaluates the legal and political impacts of this change and its implications for Indonesia's electoral system. Based on an analysis of legal documents and data from the Central Bureau of Statistics (BPS), the study finds that youth political participation is expected to increase, given the dominance of the productive age population in Indonesia's demographics. This decision is anticipated to facilitate broader participation from younger generations, both as voters and potential leaders. However, debates remain regarding the experience and competence of young leadership candidates. In conclusion, the Constitutional Court's decision reflects a move towards a more inclusive democracy but requires additional policies to ensure that young leaders elected possess adequate capacity to manage governance.